Molecular cloning, characterization, and expression of the Tipula iridescent virus capsid gene. - Tajbakhsh, S (1990)
The capsid protein is the major structural component of the icosahedral Tipula iridescent virus (TIV) that replicates in cytoplasmic inclusion bodies of insect cells. TIV capsid protein purified by sodium dodecyl sulfate-polyacrylamide gel electrophoresis was digested with trypsin and fractionated by reverse-phase high-pressure liquid chromatography. A mixed oligonucleotide constructed from the amino acid sequence of a capsid tryptic peptide was used for the identification and cloning of the corresponding gene. The single-copy capsid gene, located on a 2.47-kilobase-pair HindIII TIV genomic fragment, codes for a 464-amino-acid protein (50,831 daltons) with a predicted pI of 6.34. Analysis of total RNA from infected Estigmene acrea cells indicated that the 1.8-kilobase capsid transcript was maximally produced between 14 and 24 h after infection. Transcript mapping by primer extension indicated that the RNA start site was in the A+T-rich TGCTACTAAT sequence, 19 nucleotides upstream from the first ATG codon of the capsid open reading frame. Expression of the TIV capsid protein in infected E. acrea cells was demonstrated by in vivo labeling of total proteins with [35S]methionine, using anti-capsid antiserum as the probe. Capsid protein was also expressed in Escherichia coli cells by using a pUC19 plasmid containing a lacZ-capsid gene fusion.